Perilaku Pemerintah Indonesia Dalam Memaksimalkan Welfare (Pendekatan Rawlasian-Utilitarian) - Dwi Widiarsih; Hefrizal Handra; Efa Yonnedi (Akuntansi & Ekonomika, 2021)
The concept of utilitarian welfare in Indonesia is identically applied to the implementation of the government's fiscal capacity policy. The research design is a quantitative concept, namely an experimental design using the weights of measuring income per capital, taxes, subsidies as a function of Iriani-Tamoka welfare with the central government constraint is to maximize the social welfare of the community. The results of the study found that government behavior in setting the tax burden is identical to utilitarian behavior in maximizing the welfare of its people. The government's transfer policy through social assistance and social security which is distributed to the community as an effort by the government to maximize utility through public welfare under the constraints of subsidy allocation and the multiplier effect caused by the determination of government taxes is identical to Rawlsian's behavior.